A weilian reading by Dom Casmurro: Jealousy as radical evil - Soares, Daniel; Costeski, Evanildo (Sofia, 2022)
The paper seeks to investigate whether the Weilian concept of radical evil is enough to understand the moral behavior of Bento Santiago described in the novel Dom Casmurro by Machado de Assis. It is necessary, therefore, to outline Eric Weil’s analysis of the Kantian radical evil, which is proposed in the first section of this paper. The second section compares the Kantian concept with radical evil as it appears in Weil’s work, which marks the particularity of the version found in Eric Weil’s thought of the inspiration of Kantian radical evil. In the third section of the paper, Weil’s radical evil – understood as passionate violence – is applied to Bento Santiago’s actions and then analyzes its suitability and sufficiency for understanding the Machadian memorialist’s behavior. The conclusion of the paper aims to answer if the concept is enough to account for the moral violence of the case studied. Resumo Propõe-se investigar se o conceito weiliano de mal radical basta para compreender o comportamento moral de Bento Santiago descrito no romance Dom Casmurro. É necessário para tanto traçar em linhas gerais a análise feita por Eric Weil do mal radical kantiano, o que é proposto na primeira seção do artigo. Feito isso, o conceito kantiano é comparado com o mal radical conforme aparece na obra weiliana, o que marca a particularidade da versão encontrada no pensamento de Eric Weil da inspiração do mal radical kantiano; esse é o tema da segunda seção. Finalmente, o mal radical weiliano – entendido como violência passional – é aplicado ao agir de Bento Santiago para então analisar sua adequação e suficiência para a compreensão do comportamento do memorialista machadiano, o que é feito na terceira seção do artigo. Essa análise permite responder se o conceito basta para dar conta da violência moral do caso estudado.